The Effect of Ball Size on Hardness of Mechanically Alloyed Al-10wt.%Ti Powders - Adolf Asih Supriyanto; Widodo Widodo; Ade Irvan Tauvana; Syafrizal Syafrizal (International Journal of Advanced Technology, 2020)
Particle size and hardness of Al-10%wt.Ti powders due to the influence of ball diameter have been carried out using mechanical alloying techniques. The milling device used consisted of a Fritsch Pulverisette-5 planetary type ball mill with the rotational speed of about 360 rpm and balls size of 10, 15 and 20 mm. The materials used are stearic acid which was used as a process control agent, aluminum and titanium powders. A mixture of aluminum and titanium powders has the composition of Al-10wt.%Ti. The Al-10wt.%Ti powders, stearic acid and stainless-steel balls were added to the Fritsch Pulverisette-5 planetary in the argon gas environment. The weight ratio of stainless steel balls to the Al-10wt.%Ti powder was 20 : 1. The mixing time process was carried out for 5, 10, 15, 20 and 30 hours, respectively. Changes in phase compositions of these Al-Ti powders under different ball mill sizes were examined by XRD, and the optimum experimental parameter was obtained: the ball mill size was 20 mm. It was found that from the diffraction patterns of the Al-10wt.%Ti powders, the peaks of titanium begin to disappear with the increasing of the milling time, which indicates the increasing degrees of alloying of titanium atoms in the aluminum matrix. The microhardness test results showed that the hardness increases with increasing ball size.